Perencanaan Pembangunan Infrastruktur Pasca Era New Normal di Kotawaringin Timur Provinsi Kalimantan Tengah - Nenty Maurina Melia Gessy; Salahudin Salahudin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
New normal is a policy of reopening economic, social and public activities on a limited basis using health standards that did not exist before the Covid-19 pandemic. New normal becomes a new stage after the policy of stay at home or work from home when large-scale social restrictions (PSBB) are imposed to prevent the spread of massif coronavirus outbreak. Handling corona virus is a top priority, but that does not mean development should be stagnant. Therefore, just before the start of the new normal, President Jokowi has held a virtual limited meeting discussing the evaluation of the National Strategic Project for national economic recovery impact of Covid-19. This study aims to find out the planning of infrastructure development after the new normal era in East Kotawaringin. The method used is review paper using vosviewer software. In addition by using papper review authors can also see the shortcomings of of previous researchers so as to make improvements and formulation more regularly.